Optical networking and real-time provisioning an integrated vision for the next-generation Internet. - Assi, C. (IEEE Network : the magazine of global information exchange)
This article considers the problem of real-time provisioning of optical channels in hybrid IP-centric DWDM-based networks. First, we present an overview of the emerging architectural alternatives for IP over optical networks, namely, the overlay, the peer, and the augmented models. Then lightpath provisioning issues are detailed for route selection, with a particular focus on the ?routing and wavelength assignment? (RWA) problem. In particular, a broad overview is presented, with methodologies and associated algorithms for dynamic lightpath computation being outlined. Additionally, two broad constraint-based RWA algorithms for dynamic provisioning of the optical channels are presented and evaluated. Finally, the implications of implementing the proposed RWA schemes for the lightpath provisioning aspects for each of the three emerging IP over optical network interconnection models are examined